2015
DOI: 10.4097/kjae.2015.68.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Does spinal stenosis correlate with MRI findings and pain, psychologic factor and quality of life?

Abstract: BackgroundTo investigate and analyze MRI findings in relation to visual analogue scale (VAS), Oswestry Disability Index (ODI), psychological-factor, sleep-quality, and Short-Form Health Survey (SF-36) scores among patients with central lumbar spinal stenosis (LSS) for the purpose of elucidating a correlation.MethodsFrom July 2013 to May 2014, 117 consecutive patients with central LSS were included in this study. All of the MRIs were evaluated by one of the authors, and the evaluated items were the dural sac cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
9
13
2
Order By: Relevance
“…The number of slipped vertebrae affected the severity of disability ( p = .033), where patients with more slipped vertebrae tended to experience more severe disabilities. This result is consistent with that of Hong Lee Jung and Lee (). The intensity of LBP and leg pain also influenced the degree of disability ( p = .023; p = .001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The number of slipped vertebrae affected the severity of disability ( p = .033), where patients with more slipped vertebrae tended to experience more severe disabilities. This result is consistent with that of Hong Lee Jung and Lee (). The intensity of LBP and leg pain also influenced the degree of disability ( p = .023; p = .001).…”
Section: Discussionsupporting
confidence: 93%
“…The intensity of leg pain increases the likelihood of undergoing depression. These findings are similar to those of Hong et al (). This study also discovered that patients who were more satisfied with their level of family support tended to have a lower level of depression, which is consistent with past studies (Hung et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It typically presents with buttock or low back pain, sensory and motor disturbances in the lower leg, and neurogenic intermittent claudication [2, 4]. LSS is characterized by narrowing of the spinal canal, which is caused by disc herniation combined with osteophytes, hypertrophy of the ligamentum flavum, and mechanical compression of the spinal nerve roots [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The foramen can be narrowed further by characteristic changes in the facet joints such as synovial cysts, osteoarthritis, or hypertrophy of articular processes [8, 9]. All of the changes contribute to LFS symptoms [4, 5]. Previous studies have indicated that morphologic parameters including the dural sac area, spinal canal area, and ligamentum flavum thickness are associated with disc degeneration, aging, and LSS [1012].…”
Section: Introductionmentioning
confidence: 99%
“…There are now several studies that support the role of social and psychological variables, including depression, anxiety, mental state, or patient personality, in affecting the results of spinal surgery,8–10 with depression having a recognized negative association 10,11. For more than a decade, since the publication of the standard text by Block et al,12 it has been known that, in the context of spinal surgery, reactive depression can be both a response to chronic pain and to the subsequent limitations that result from pain and limitation of movement and function, such as loss of employment, social life, and friends.…”
Section: Introductionmentioning
confidence: 99%